EFFECT OF Leptospira sp. INFECTION ON REPRODUCTIVE EFFICIENCY OF A CROSSBREED CATTLE HERD IN THE SOUTH OF BAHIA STATE, BRAZIL - Lopes, Luciano Bastos; Júnior, Antônio Claret Oliveira; de Melo, Cristiano Barros; McManus, Concepta; Leite, Rômulo Cerqueira (Brazilian Journal of Veterinary Medicine, 2010)
ABSTRACT. Lopes L.B., Oliveira Junior A.C., Melo C.B. de, McManus C. & Leite R.C. Effect of Leptospira sp. infection on reproductive efficiency of a crossbreed cattle herd in the South of Bahia State, Brazil. [Efeito da infecção por Leptospira sp. na eficiência reprodutiva de um rebanho bovino mestiço no Sul da Bahia]. Revista Brasileira de Medicina Veterinaria, 32(1):51-54, 2010. Universidade de Brasília, Campus Universitário Darcy Ribeiro, Asa Norte, ICC Sul, Caixa Postal 4508, Brasília, DF 70910-970, Brasil. E-mail: cristianomelo@unb.br Brazilian animal production is under the world spotlight due to the increase in production and exportation of cattle and beef. Despite positive results in animal production in recent years, reproductive performance in some herds continues to be below optimum due to various factors, including infectious diseases that affect reproduction. Reproductive performance in a crossbred zebu herd was evaluated through number of inseminations per pregnancy associated with serology for Leptospira sp. No association was found between serological profile and reproductive performance of the tested animals.